Pengaruh Terapi Berendam Air Laut Terhadap Penurunan Kadar Asam Urat Di Wilayah Kerja Puskesmas Burau - Mailani Fasyipha Zahrah Rahman; Masriadi; Nur Ulmy Mahmud (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Uric acid is the final metabolic result of purine, a component of nucleic acids found in the nucleus of body cells. Increased uric acid levels can cause disorders in the human body, such as joint pain, and are often accompanied by the emergence of extreme pain for sufferers. This study aims to determine the effect of seawater immersion therapy on reducing uric acid levels in women in the working area of ​​the Burau Community Health Center, East Luwu Regency. This study uses a quantitative approach, an observational-analytical survey, and a cross-sectional design. This type of research is a quantitative study with a true experimental research design (true experiment): Pretest-Posttest With Control Group. The population of this study comprised all individuals in the working area of the Burau Community Health Center, and the research sample consisted of 15 respondents from the Burau Community Health Center in East Luwu Regency, using a purposive sampling method. The study's results were obtained from data collected during an examination. A data normality test was then conducted, and the data were analyzed using a paired-samples t-test, which showed that seawater immersion therapy reduced uric acid levels (p-value = 0.001 < 0.05). This study concludes that seawater bathing therapy reduces uric acid levels in the Burau Health Center's working area, East Luwu Regency.